Improving sensitivity to eye gaze cues in adolescents on the autism spectrum using serious game technology: A randomized controlled trial - Jason W. Griffin; Charles F. Geier; Joshua M. Smyth; K. Suzanne Scherf (Wiley, 2021)
Abstract Background Perceiving and interpreting eye gaze cues is foundational for social cognition and social interactions because it involves the ability to use eye gaze direction to predict the actions and intentions of others. Autism is a disability that impacts social interactions. A diagnostic symptom of autism is difficulty understanding eye gaze cues as social signals. This deficit has long‐term consequences for understanding goal‐directed behavior, language learning, and social communication. We hypothesize that targeted intervention methods designed to improve sensitivity to eye gaze cues may begin to treat core symptoms of autism and potentially alter multiple aspects of social functioning. Social Games for Autistic Adolescents (SAGA) is a serious computer game intervention designed to improve sensitivity to eye gaze cues. Serious games improve targeted skills with the goal of enhancing real‐life outcomes. In SAGA, participants progress through a narrative storyline and interact with animated characters. In so doing, they implicitly discover that eye gaze cues are useful for guiding their own goal‐directed behavior to solve problems in the game. Methods We evaluated the feasibility and effectiveness of SAGA in a hybrid phase 1/2, randomized controlled trial. Forty adolescents on the autism spectrum were randomized to either the treatment or standard care control group. Adolescents in the treatment group were asked to play SAGA for 30‐min sessions at home 3 times a week over 10 weeks. Results A group × time interaction revealed that the treatment group developed increasing sensitivity to human eye gaze cues, whereas the standard care group did not. Participants who experienced a sufficient dose of gameplay showed larger treatment‐related improvements. Critically, increases in sensitivity to human eye gaze cues were associated with improvements in social skills. Conclusions This accessible, scalable, and affordable intervention shows promise as an effective tool for improving the ability to interpret and understand eye gaze cues and social skills in adolescents on the autism spectrum.